The Right to Water in Uganda Perspectives from the district of Kayunga - Sandoval, Rita Michelle (Initiative for Social and Economic Rights (ISER), 2014)
Access to safe and clean water in adequate quantities in Uganda remains a major impediment to the country’s human development. Uganda is among the least developed nations in the world, ranking 162 out of 184 nations on UNDP’s 2013 Human Development Index—which ranks countries utilizing data on life expectancy, income and educational attainment1. In Uganda an estimated 9.2 million people do not have access to clean and safe water and are thus unable to enjoy their human right to water2. Limited access to safe water and subsequently adequate sanitation thus compromises the right to health of a large proportion of the country’s population.